Discordance in latent tuberculosis (TB) test results in patients with end-stage renal disease. (January 2019) - Southern, J.; Sridhar, S.; Tsou, C.-Y.; Hopkins, S.; Collier, S.; Nikolayevskyy, V.; Lozewicz, S.; Lalvani, A.; Abubakar, I.; Lipman, M.
Abstract: Objectives: This natural experiment was designed to assess the impact of exposure to an active case of tuberculosis (TB) on a group of immunosuppressed individuals, with end-stage renal disease over an extended follow-up. Study design: Close contacts of people with sputum smear–positive Mycobacterium tuberculosis are at high risk of infection, particularly immunosuppressed individuals. An infectious TB healthcare worker worked in a renal dialysis unit for a month before diagnosis, with 104 renal dialysis patients, was exposed for ≥8 h. Methods: Patients were informed and invited for screening 8–10 weeks postexposure. They either underwent standard two-step assessment with tuberculin skin test (TST) and QuantiFERON ® -TB Gold (Cellestis GmbH; QFN) interferon-gamma release assay (IGRA) or after consent, enrolled in a study where these two tests were performed simultaneously with T-SPOT ® -TB (Oxford Immunotec Ltd; TSPOT). Patients within the study were followed up for 2 years from exposure, with QFN and TSPOT repeated at months 3 and 6 from the first testing. Results: Of 104 exposed individuals, 75 enrolled in the study. There was a high degree of discordance among QFN, TSPOT and TST. This was seen at both the first time point and also over time in subjects who were retested. No patients had active TB at the baseline testing. None received treatment for latent TB infection. Over the following 2 years, no one developed TB disease. Conclusion: This study suggests that there is a low risk of progression to active TB in low-incidence countries even in high-risk groups. This plus the degree of the test result discordance emphasises the complexities of managing TB in such settings as it is unclear which of these tests, if any, provides the best diagnostic accuracy. Highlights: The high degree of discordance found in latent tuberculosis (TB) diagnostic tests in patients with end-stage renal disease, plus the apparently low progression from latent TB infection to active disease, makes management of latent TB infection complex in this patient population.